Novel 3-D Printable Aspiration Device “SPUTA VACUUMER” Designed to Minimize Invasion - Naoyuki Ishikita (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: The purpose of this study is to develop a minimally invasive sputum aspiration device. Methods: The current general method is to insert a suction catheter into the trachea. However, sufficient suction cannot be obtained unless the catheter reaches the target. A new connection device “SPUTA VACUUMER” has been invented. The effectiveness of the SPUTA VACUUMER is tested in this study. Results: After manually inflating the lungs, the device applies suction pressure to the entire lungs. Peripheral sputum or foreign matter is effectively moved to the upper respiratory tract. Conclusions: “SPUTA VACUUMER” is minimally invasive, simple and cost effective. The device can be manufactured with a 3D printer and the plastic injection molding model received pharmaceutical approval in Japan in 2021. It is currently being used in clinical settings. It can be operated by non-skilled personnel and may be performed in space and improve astronauts' quality of life.